Intravitreal bevacizumab for subfoveal choroidal neovascularization in age-related macular degeneration at twenty-four months: The pan-american collaborative retina study (2010)
Purpose: To report the 24-month anatomic and Early Treatment Diabetic Retinopathy Study (ETDRS) best-corrected visual acuity (BCVA) response after primary intravitreal bevacizumab (IVB) (Avastin; Genentech Inc., San Francisco, CA) (1.25 or 2.5 mg) in patients with subfoveal choroidal neovascularization (CNV) secondary to age-related macular degeneration (AMD). Design: Retrospective, multicenter, interventional, comparative case series. Participants: We reviewed the clinical records of 180 consecutive patients (207 eyes) with subfoveal CNV secondary to AMD at 9 centers from 8 countries. Methods: Patients were treated with at least 1 injection of IVB 1.25 mg (124 eyes [59.9%]) or 2.5 mg (83 eyes [40.1%]). Patients underwent ETDRS BCVA testing, ophthalmoscopic examination, optical coherence tomography (OCT), and fluorescein angiography (FA) at baseline and 1-, 3-, 6-, 12-, and 24-month visits. Main Outcome Measures: Changes in BCVA and OCT. Results: The mean age of our patients was 74.3±7.5 years. The mean number of IVB injections per eye was 5.1 (range, 124 injections). In the 1.25 mg group, baseline BCVA improved from 20/235 (logarithm of the minimum angle of resolution [logMAR] 1.07) to 20/172 (logMAR 0.92) at 24 months (P less than 0.0001). Similar BCVA changes were observed in the 2.5 mg group. At baseline, the mean central macular thickness (CMT) by OCT in the 1.25 mg group was 308.4±127.52 ?m, which was reduced to 269.35±97.92 ?m, 262.1±94.81 ?m, 264.03±97.06 ?m, 245.91±89.52 ?m, and 249.27±89.14 ?m at 1, 3, 6, 12, and 24 months, respectively (P less than 0.0001). Similar changes were observed in the 2.5 mg group. In the 2.5 mg group, systemic complications included 2 new cases (2.6%) of arterial hypertension, 1 case (1.3%) of stroke, and 1 case (1.3%) of death. Conclusions: Primary IVB at a dose of 1.25 or 2.5 mg seems to provide stability or improvement in BCVA, OCT, and FA in subfoveal CNV secondary to AMD at 24 months. Our results show no significant difference regarding BCVA with IVB at doses of 1.25 or 2.5 mg. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article. © 2010 American Academy of Ophthalmology.